Hubungan Tingkat Spiritualitas Wanita Menopause dengan Sindrom Menopause pada Daerah Pedesaan - Intan Indah Sari; Sari Sudarmiati (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2021)
Introduction: Menopausal women experience a number of symptoms called menopausal syndrome. Previous study) states that menopausal syndrome in women in Europe reaches 70-80%, Americans 60%, Malaysia 57%, China 18%, Japan and in Indonesia 10%. The prevalence and severity of menopausal syndrome in Asia show lower rates than women in Western. Another  study states, high spiritual well-being can provide adaptive coping and contribute to reducing menopausal symptoms. Studies on the relationship between the spiritual level of menopausal women and menopausal syndrome in rural areas are still limited. The study aims to determine the relationship of spirituality levels with menopausal syndrome in rural area.  Method: This study is  correlation research  with cross sectional approach. Number of samples is 207 women. The sampling technique used stratified random sampling. The research was conducted in Tangkisan Village, Tawangsari District, Sukoharjo Regency. Instruments used in this study is  Spiritual Well-Being Scale (SWBS) to measure spirituality levels and Menopausal Rating Scale (MRS) to determain the level of menopausal syndrome. The quesionnare distributed online by whatsapp.using google form.  Data analysis using  using Spearman rank test. Result: The analysis showed that there was a significant relationship between the level of spirituality with menopausal syndrome in women with a correlation value of -0,300 and p value ≤ 0,05.Conclusion: A high level of spirituality reduced menopausal syndrome. Menopausal women are expected to prepare and improve their spirituality to be more ready to undergo menopause.